Genome-wide identification and expression analysis of the AS2/LOB gene family in physic nut - Tang, Yuehui; Wang, Xiaohui; Feng, Jiayu; Wang, Yaoyao; Liu, Tengfei; Bao, Xinxin (Frontiers in Plant Science, 2024)
Abstract：AS2/LOB genes, a class of transcription factors ubiquitously existing in plants, are vital for plant growth, development, and stress tolerance. Despite the availability of the physic nut genome, information regarding the expression profiles and evolutionary histories of its AS2/LOB genes remains scarce. In this study, 28 AS2/LOB genes (JcASLs) were identified in the physic nut genome, and an elaborate exploration of the AS2/LOB gene family was conducted, including phylogeny, exon-intron structure, chromosomal location, conserved domain characteristics, conserved motifs, promoter cis-acting elements, protein interaction, and expression profiles under normal growth and abiotic stress conditions. Phylogenetic analysis, based on homologs from Arabidopsis, classified the 28 JcASLs genes into two groups (calss I and II).Chromosome localization indicated that the 28 JcASLs genes were unevenly distributed across nine chromosomes. RNA-seq and qRT-PCR results revealed that the majority of the 28 JcASLs genes exhibited differential expression in tissues such as roots, cortex stems, leaves, and seeds. Notably, JcASL8 and JcASL13 were exclusively expressed in seeds, and 16 JcASLs genes responded to drought and salt stress at least at one time point under at least one treatment condition. These results establish a basis for future investigations into the molecular mechanism by which the JcASLs genes regulate physic nut's response to drought and salt stress and their role in modulating the growth and development of physic nut.